ASCETICISM IN ISLAMIC RELIGIOUS EDUCATION - Kambali Kambali (al-Afkar, Journal For Islamic Studies, 2020)
Islamic religious education is not solely about discussing how Muslims carry out their religious teachings, but it also discusses issues with a wider range of educational interests capable of creating human happiness and success in the world and the hereafter. For this reason, a proper education system must be created so that it can produce humanity in accordance with Islamic teachings. Reformation in Islamic education requires the contextualization of Islamic religious education in accordance with the original sources in the Qur'an and Assunnah so that there is a relevance between Islamic religious education and current situations. Although Islamic education keeps updated to the current situation, spiritual values (asceticism) and ahlakul karimah are not abandoned. The spiritual values (asceticism) in relation to Islamic religious education must be developed and taught, but how to teach and internalize them to people, especially to students, requires basic thoughts and findings so that ascetic attainment of Islamic religious education can be reached.